Comparative in vivo toxicity, organ biodistribution and immune response of pristine, carboxylated and PEGylated few-layer graphene sheets in Swiss albino mice: A three month study. (December 2015) - Sasidharan, Abhilash; Swaroop, Siddharth; Koduri, Chaitanya K.; Girish, Chundayil Madathil; Chandran, Parwathy; Panchakarla, L.S.; Somasundaram, Vijay H.; Gowd, Genekehal S.; Nair, Shantikumar; Koyakutty, Manzoor
Abstract: We present a comprehensive 3 month report on the acute and chronic toxicity of intravenously administered (20 mg kg −1 ) few-layer graphene (FLG) and, its carboxylated (FLG-COOH) and PEGylated (FLG-PEG) derivatives in Swiss albino mice. Whole-animal in vivo tracking studies revealed that irrespective of surface modifications, graphene predominantly accumulated in lungs over a period of 24 h. Histological assessment and ex vivo confocal Raman spectral mapping revealed highest uptake and retention in lung tissue, followed by spleen, liver and kidney, with no accumulation in brain, heart or testis. FLG and FLG-COOH accumulated within organs induced significant cellular and structural damages to lungs, liver, spleen, and kidney, ranging from mild congestion to necrosis, fibrosis and glomerular filtration dysfunction, without appreciable clearance. Serum biochemistry analysis revealed that both FLG and FLG-COOH induced elevated levels of hepatic and renal injury markers. Quantitative RT-PCR studies conducted on 23 critical inflammation and immune response markers showed major alterations in gene expression profile by FLG, FLG-COOH and FLG-PEG treated animals. FLG-PEG in spite of its persistance within liver and spleen tissue for 3 months, did not induce any noticeable toxicity or organ damage, and displayed significant changes in Raman spectra, indicative of their biodegradation potential. Graphical abstract: